More than just antibodies: Protective mechanisms of a mucosal vaccine against fish pathogen Flavobacterium columnare. Issue 71 (December 2017) - Zhang, Dongdong; Thongda, Wilawan; Li, Chao; Zhao, Honggang; Beck, Benjamin H.; Mohammed, Haitham; Arias, Covadonga R.; Peatman, Eric
Abstract: A recently developed attenuated vaccine for Flavobacterium columnare has been demonstrated to provide superior protection for channel catfish, Ictalurus punctatus, against genetically diverse columnaris isolates. We were interested in examining the mechanisms of this protection by comparing transcriptional responses to F. columnare challenge in vaccinated and unvaccinated juvenile catfish. Accordingly, 58 day old fingerling catfish (28 days post-vaccination or unvaccinated control) were challenged with a highly virulent F. columnare isolate (BGSF-27) and gill tissues collected pre-challenge (0 h), and 1 h and 2 h post infection, time points previously demonstrated to be critical in early host-pathogen interactions. Following RNA-sequencing and transcriptome assembly, differential expression (DE) analysis within and between treatments revealed several patterns and pathways potentially underlying improved survival of vaccinated fish. Most striking was a pattern of dramatically higher basal expression of an array of neuropeptides (e.g. somatostatin), hormones, complement factors, and proteases at 0 h in vaccinated fish. Previous studies indicate these are likely the preformed mediators of neuroendocrine cells and/or eosinophilic granular (mast-like) cells within the fish gill. Following challenge, these elements fell to almost undetectable levels (>100-fold downregulated) by 1 h in vaccinated fish, suggesting their rapid release and/or cessation of synthesis following degranulation. Concomitantly, levels of pro-inflammatory cytokines (IL-1b, IL-8, IL-17) were induced in unvaccinated fish. In contrast, in vaccinated catfish, we observed widespread induction of genes needed for collagen deposition and tissue remodeling. Taken together, our results indicate an important component of vaccine protection in fish mucosal tissues may be the sensitization, proliferation and arming of resident secretory cells in the period between primary and secondary challenge. Highlights: Vaccinated catfish had a higher basal expression of many preformed mediators. Proteases and neuropeptide level in vaccinated fish fell rapidly following challenge. Collagen deposition and tissue remodeling processes were induced in vaccinated fish. Pro-inflammatory genes were upregulated in unvaccinated fish post challenge.